PENGARUH MODEL PEMBELAJARAN IPAE TERHADAP KEMAMPUAN BERPIKIR ANALITIS DAN SIKAP ILMIAH SISWA PADA PEMBELAJARAN IPA DI SMP - Tri Desyanti; Joko Siswanto; Harto Nuroso (Universitas PGRI Semarang, 2015)
Based on the results of the literature studies showed that the implementation of teacher-centered learning model is still frequently performed and causes a lower analytical thinking ability and scientific attitude of students, so it is necessary to develop. Inquiry-based learning can be implemented through the application of learning models IDAE so expect the analytical thinking ability and scientific attitude of students can be increased. This study aims to determine the effects of the IDAE learning model to analytical thinking ability and scientific attitude of students in science teaching in the junior high class VII in the materials of heat. The design of this study is Pre Experimental Design by using one group pre-test and post-test. Data collected by test method for analytical thinking ability , questionnaires and observations for scientific attitude. The results showed that the implementation of learning models IDAE have a positive and significant influence but it is included in the low criteria for analytical thinking ability and scientific attitude of students.